A case of toxic epidermal necrolysis caused by trimethoprim-sulfamethoxazole. (9th July 2014) - Rijal, Jharendra P; Pompa, Tiffany; Giri, Smith; Bhatt, Vijaya Raj
Abstract : Toxic epidermal necrolysis (TEN) is a rare but serious dermatological emergency characterised by diffuse exfoliation of the skin and mucous membranes due to immune mediated destruction of the epidermis which can lead to sepsis and respiratory distress. Trimethoprim-sulfamethoxazole is a widely used antibiotic which can rarely lead to TEN. Early diagnosis and aggressive medical care is essential for the reduction of high morbidity and mortality associated with this disease. We present a case of successfully recovered TEN due to trimethoprim-sulfamethoxazole in a 62 -year-old woman.